1-1-1-1-1-1-1-1-1-1-1-1-1-1-1x-2x-3-456g-a=g

Simple and best practice solution for 1-1-1-1-1-1-1-1-1-1-1-1-1-1-1x-2x-3-456g-a=g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-1-1-1-1-1-1-1-1-1-1-1-1-1-1x-2x-3-456g-a=g equation:


Simplifying
1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1x + -2x + -3 + -456g + -1a = g

Reorder the terms:
1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: 1 + -1 = 0
0 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g
-1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -1 + -1 = -2
-2 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -2 + -1 = -3
-3 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -3 + -1 = -4
-4 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -4 + -1 = -5
-5 + -1 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -5 + -1 = -6
-6 + -1 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -6 + -1 = -7
-7 + -1 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -7 + -1 = -8
-8 + -1 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -8 + -1 = -9
-9 + -1 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -9 + -1 = -10
-10 + -1 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -10 + -1 = -11
-11 + -1 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -11 + -1 = -12
-12 + -3 + -1a + -456g + -1x + -2x = g

Combine like terms: -12 + -3 = -15
-15 + -1a + -456g + -1x + -2x = g

Combine like terms: -1x + -2x = -3x
-15 + -1a + -456g + -3x = g

Solving
-15 + -1a + -456g + -3x = g

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + -1a + -456g + 15 + -3x = 15 + g

Reorder the terms:
-15 + 15 + -1a + -456g + -3x = 15 + g

Combine like terms: -15 + 15 = 0
0 + -1a + -456g + -3x = 15 + g
-1a + -456g + -3x = 15 + g

Add '456g' to each side of the equation.
-1a + -456g + 456g + -3x = 15 + g + 456g

Combine like terms: -456g + 456g = 0
-1a + 0 + -3x = 15 + g + 456g
-1a + -3x = 15 + g + 456g

Combine like terms: g + 456g = 457g
-1a + -3x = 15 + 457g

Add '3x' to each side of the equation.
-1a + -3x + 3x = 15 + 457g + 3x

Combine like terms: -3x + 3x = 0
-1a + 0 = 15 + 457g + 3x
-1a = 15 + 457g + 3x

Divide each side by '-1'.
a = -15 + -457g + -3x

Simplifying
a = -15 + -457g + -3x

See similar equations:

| 5x-6-3x=4 | | 5x-5-6x=-6 | | 9x=8x-8 | | 2x+2x=3x+5x+1-5 | | 4-3x+5(2-x)=6(x+9) | | 5x+2-2x=8 | | 9n^2+16=-24n | | 5+5x=-50 | | 5x+-2-2x=8 | | 6(2x-1)-12=7+12(x+1) | | -0.875-(-n)=-0.583 | | m+6m+5m+8= | | 9=-5p+5+6p | | 4(2x+5)-18=36 | | -3=9p-9-8p | | (8)(16)=(6)(2x+6) | | 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 |

Equations solver categories